(untitled) (Bioscience Journal, 2018)
: Lactic acid bacteria are used as starter culture for the production of fermented dairy products, and that occur naturally as indigenous microbiota of the raw milk. In this study, lactic acid bacteria were isolated from raw cow milk samples. The serial dilutions of raw milk were made and plated onto LM17 agar and MRS agar adjusted to pH 5.4. The isolates were firstly identified based on cell morphology, reaction to gram stain, catalase production, growth in MRS broth containing 2%, 4%, and 6.5% NaCl, growth ability of different temperatures and formation of gas in MRS broth. Acid formation in 10% reconstituted skim milk and antimicrobial activity against foodborne pathogens Listeria monocytogenes ATCC 7644, Stapylococcus aureus ATCC 25923, and Clostridium perfringens ATCC 13124 were examined using agar well diffusion method. The total of 90 LAB isolates were classified as Lactobacillus (37.78%), Lactococcus (36.67%), Enterococcus (20.00%), Streptococcus (4.44%), and Leuconostoc (1.11%). Based on technological properties, 56 of 90 isolates (42 cocci, 14 rods) were selected, and further identified at the species level using API 20 Strep and API 50 CH identification system, respectively. The Lactobacillus isolates were identified as Lactobacillus acidophilus, Lactobacillus fermentum, Lactobacillus paracasei ssp. paracasei, Lactobacillus plantarum, Lactobacillus delbrueckii ssp. lactis, and Lactobacillus rhamnosus. The enzymatic profiles of the 17 selected isolates were studied with API ZYM system. The Lactobacillus spp. strains tested displayed high leucine arylamidase activity. Two Lactococcus lactis ssp. lactis AKS320.1 and AKS320.2 strains and one Enterococcus faecalis AKS424 strain were able to produce bacteriocin. In conclusion, some of these isolates could be considered as potential starter culture candidates for fermented milk products.